Thermoplasmonic‐Activated Hydrogel Based Dynamic Light Attenuator. Issue 12 (21st April 2020) - Pierini, Filippo; Guglielmelli, Alexa; Urbanek, Olga; Nakielski, Pawel; Pezzi, Luigia; Buda, Robert; Lanzi, Massimiliano; Kowalewski, Tomasz A.; De Sio, Luciano
Abstract: This work describes the morphological, optical, and thermo‐optical properties of a temperature‐sensitive hydrogel poly( N ‐isopropylacrylamide‐ co ‐ N ‐isopropylmethacrylamide) [P(NIPAm‐ co ‐NIPMAm]) film containing a specific amount of gold nanorods (GNRs). The light‐induced thermoplasmonic heating of GNRs is used to control the optical scattering of an initially transparent hydrogel film. A hydrated P(NIPAm‐ co ‐NIPMAm) film is optically clear at room temperature. When heated to temperatures over 37 °C via light irradiation with a resonant source (λ = 810 nm) to the GNRs, a reversible phase transition from a swollen hydrated state to a shrunken dehydrated state occurs. This phenomenon causes a drastic and reversible change in the optical transparency from a clear to an opaque state. A significant red shift (≈30 nm) of the longitudinal band can also be seen due to an increased average refractive index surrounding the GNRs. This change is in agreement with an ad hoc theoretical model which uses a modified Gans theory for ellipsoidal nanoparticles. Morphological analysis of the composite film shows the presence of well‐isolated and randomly dispersed GNRs. Thermo‐optical experiments demonstrate an all‐optically controlled light attenuator (65% contrast ratio) which can be easily integrated in several modern optical applications such as smart windows and light‐responsive optical attenuators. Abstract : A thermoplasmonic activated light beam attenuator is obtained by bridging the photothermal properties of gold nanorods and the thermoresponsivity of a hydrated hydrogel film. The sample is optically clear at room temperature whereas when photoheated to temperatures over 37 °C, via light irradiation a reversible phase transition produces a reversible change in the optical transparency.